2010
DOI: 10.1016/s0828-282x(10)70371-8
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of circulating microparticles in inflammation, coagulation and cardiovascular diseases

Abstract: Microparticles (MPs) are small vesicles, ranging in size from 0.1 microm to 2 microm, originating from plasma membranes of endothelial cells, platelets, leukocytes and erythrocytes. MPs can transfer antigens and receptors to cell types that are different from their cell of origin. Circulating MPs provide a procoagulant aminophospholipid surface for the assembly of the specific enzymes of coagulation. Both tissue factor and phosphatidylserine are exposed on MP outer membranes. In addition, MPs can play a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 105 publications
(92 reference statements)
2
137
0
Order By: Relevance
“…[13][14][15] The externalization of PS indicates the loss of the integrity of the membrane that in the vascular disease, is the final expression of endothelial injury or trauma. 3,4,16 Apoptosis, a programmed cell death, has an important role in the initiation and progression of a number of cardiovascular disease, such as heart failure, myocardial infarction and atherosclerosis. One of the most prominent characteristics of apoptosis is the externalization of PS, a plasma cell membrane phospholipid, which in healthy cells only is present on the inner leaflet of the plasma cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The externalization of PS indicates the loss of the integrity of the membrane that in the vascular disease, is the final expression of endothelial injury or trauma. 3,4,16 Apoptosis, a programmed cell death, has an important role in the initiation and progression of a number of cardiovascular disease, such as heart failure, myocardial infarction and atherosclerosis. One of the most prominent characteristics of apoptosis is the externalization of PS, a plasma cell membrane phospholipid, which in healthy cells only is present on the inner leaflet of the plasma cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte-endothelial interaction and subsequent transendothelial migration of leukocytes are the early stage events in the development of atherosclerosis [73] . In vitro experiments have demonstrated that MVs derived from apoptotic endothelial cells or activated platelets act as cellular effectors, disseminating pro-inflammatory and pro-adhesive potentials in the vasculature [64,74] .…”
Section: Mvs and Vascular Inflammationmentioning
confidence: 99%
“…In vitro and ex vivo experiments have shown that MVs might cause endothelial dysfunction by decreasing both nitric oxide (NO) and prostacyclin production in endothelial cells [73] . Coincubation of endothelial-derived MVs with aortic rings and cultured endothelial cells causes increased superoxide production, decreased NO production, and impairment of acetylcholine-induced vasorelaxation [77] .…”
Section: Mvs and Endothelial Dysfunctionmentioning
confidence: 99%
“…This suggests a link between MPs and inflammation [4]. Their role in transferring bioactive molecules such as antigens and receptors away from their site of origin, to where they are needed, has been discovered [6]. Because of their role in various disease states they have become a popular therapeutic target for various drugs, which will be described later.…”
Section: Definition and Origin Of Mpsmentioning
confidence: 99%
“…The technique used most commonly is flow cytometry or fluorescence-activated cell sorting (FACS) [6]. However, a universal protocol for the processing of the samples has not been agreed upon by all despite a number of consensus meetings.…”
Section: Flow Cytometrymentioning
confidence: 99%